Character Analysis of the Ular Novel - Kalpana Luitel; Durga Prasad Dahal (Interdisciplinary Journal of Management and Social Sciences, 2025)
This article titled Characterization of the Novel ‘Ular’ aims to analyze the characters of the Ular novel on the basis of gender, action, tendency, nature, consciousness of life, proximity, affiliation, dimension, environment, originality, personality, reaction and relativity. This study is qualitative in nature. This study is presented in a descriptive style. Since it is found that more male characters are used in this novel than female characters on the basis of gender, it seems that the novel depicts a patriarchal society. Since there are more secondary characters than main characters and supporting characters in this novel on the basis of role or action, it seems that only a few people are dominant in society, that is, it seems that equality is not maintained in society. The fact that more favorable characters appear in this novel than unfavorable characters reveals the positive trend of society. Since many characters appear on stage and only a few characters appear in the background in this novel, it seems that the novel is moving towards a direct depiction of society. Since all the characters except Premlalwa are motionless in terms of nature, this novel seems to be unable to depict the dynamic trends of today’s modern people. In terms of life consciousness, all the characters in this novel are of a class nature, so it seems that the novel represents different classes of society. In terms of affiliation, since free characters are used more than bound characters, it seems that many people in society are of an independent nature. Since flat characters are used more than round characters in this novel, there is a greater presence of simple characters in this novel. Since all the characters in this novel are of a relative nature, the lively characters of society are depicted in the novel. The use of regional characters seems to have made this novel regional. Although there are some famous characters in this novel, their roles are not traditional and are only nominal, so it seems that original characters are used here. Although some crooked characters from the wealthy class appear to have mysterious characters in this novel, most of the characters are of a primitive nature, so it seems that the novel uses understandable characters. Since few characters are extroverted in nature to express their feelings in front of society, many characters are in an environment where they cannot express their feelings.